0
$\begingroup$

The question is like this: there is a curve $\sqrt{x}+\sqrt{y}=\sqrt{c}$, where $c$ is a real number and $c > 0$. If $L$ is a tangent line, any tangent line, with only 1 x-intercept and 1 y-intercept, prove that the sum of the x, y-intercepts of $L$ is $c$.

First of all, I used implicit differenciation on the equation. $$\sqrt{x}+\sqrt{y}=\sqrt{c}$$

Then I also put a graph hereThe curvewhen c=4 (The curve when c=4)

But I still do not have idea. Thank you for looking at this question.

$\endgroup$
2
$\begingroup$

From implicit differentiation you get $y'=-\sqrt{\frac{y}{x}}$. Hence the tangent line at any point $(x_0,y_0)$ is given by $y=-\sqrt{\frac{y_0}{x_0}}(x-x_0)+y_0$. Now find the intercepts and check that there sum is $x_0+\sqrt{x_0y_0}+y_0+\sqrt{x_0y_0}=(\sqrt{x_0}+\sqrt{y_0})^2=c.$

$\endgroup$
1
$\begingroup$

Result: Let $\phi$ be the curve in the $xy$-plane defined by $\sqrt{x}+\sqrt{y}=\sqrt{c}$, where $c\in\mathbb{R}^+$, and let $L$ be a line tangent to $\phi$ with exactly one $x$-intercept $x_i$ and exactly one $y$-intercept $y_i$. Then $x_0+y_0=c$.

Proof: We implicitly differentiate $\phi$ to find the slope of $L$: \begin{align} \frac{d}{dx}\left[\sqrt{x}+\sqrt{y}\right] &= \frac{d}{dx}\left[\sqrt{c}\right] \\ \frac{1}{2\sqrt{x}}+\frac{1}{2\sqrt{y}}\cdot\frac{dy}{dx} &= 0 \\ \frac{1}{2\sqrt{y}}\cdot\frac{dy}{dx} &= -\frac{1}{2\sqrt{x}} \\ \frac{dy}{dx} &= -\sqrt{\frac{y}{x}}. \end{align} Given any point $(x_0,y_0)$ on $\phi$, the slope of $L$ through $(x_0,y_0)$ is $$\frac{dy}{dx}\bigg|_{(x_0,y_0)}=-\sqrt{\frac{y_0}{x_0}}$$ and so the rectangular equation for $L$ is \begin{align} y-y_0 &= -\sqrt{\frac{y_0}{x_0}}\left(x-x_0\right) \\ \frac{y}{\sqrt{y_0}}-\frac{y_0}{\sqrt{y_0}} &= -\frac{x}{\sqrt{x_0}}+\frac{x_0}{\sqrt{x_0}} \\ \frac{y}{\sqrt{y_0}}+\frac{x}{\sqrt{x_0}} &= \sqrt{x_0}+\sqrt{y_0} \\ \frac{x}{\sqrt{x_0}}+\frac{y}{\sqrt{y_0}} &= \sqrt{c}.\tag{Since $(x_0,y_0)$ lies on $\phi$} \end{align} We now set $y=0$ and $x=0$ to find the two intercepts of $L$, $x_i$ and $y_i$ respectively. Observe that \begin{align} \frac{x_i}{\sqrt{x_0}}+0 &= \sqrt{c} \\ x_i &= \sqrt{c\,x_0}, \end{align} and \begin{align} 0+\frac{y_i}{\sqrt{x_0}} &= \sqrt{c} \\ y_i &= \sqrt{c\,y_0}. \end{align} Finally, we sum $x_i$ and $y_i$, which yields \begin{align} x_i+y_i &= \sqrt{c\,x_0}+\sqrt{c\,y_0} \\ &= \sqrt{c}\left(\sqrt{x_0}+\sqrt{y_0}\right) \\ &= \sqrt{c}\cdot\sqrt{c} \\ &= c.\tag*{$\blacksquare$} \end{align}

$\endgroup$
1
$\begingroup$

Suppose tangent line intersect the curve at $(x_{0},y_{0})$. Then the line equation will be

$$ \frac{x}{\sqrt{x_{0}}}+\frac{y}{\sqrt{y_{0}}}=\sqrt{c} $$

Were you able to get this line equation? From here you substitute $x=0$ to find $y$ intercept and vise versa.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.